The Proteomics of Intrathecal Analgesic agents for Chronic Pain - M. Moore, David; McCrory, Connail (Current Neuropharmacology, 2017)
Chronic pain remains a challenging clinical problem with a growing socio-economic burden for the state. Its prevalence is high and many of the patients are of work age. Our knowledge regarding the pathophysiology of chronic pain is poor. The consensus view is that the central nervous system plays a key role in the persistence of pain after an initiating event has long ceased. However the specifics of this biological response to an initiating event remains unclear. There is a growing body of evidence to support the concept that a central neuroimmune response is initiated and a number of small peptides have been implicated in this process following cerebrospinal fluid analysis in patients with chronic pain. This central biosynthetic peptide response leads to a process called central sensitization. Therapy is aimed at modulating and even inhibiting this response. However current pharmacological therapeutic options are limited in efficacy with significant deleterious side effect profiles. Proteomic studies extend single molecule analysis by identifying the components of biological networks and pathways and defining their interactions. This tool offers the potential to provide a molecular overview of the biological processes involved in chronic pain. It will also facilitate examination of gene-drug interactions. This technique offers a mechanism of defining the central biological responses that result in chronic pain and this information may facilitate the development of better therapies.
Keywords: intrathecal